Between governance & underdevelopment: accumulation & Africa's "catastrophic corruption" (2000) - Szeftel, Morris (Capitalism and economic crime in Africa, 2024)
This paper explores aspects of the tension between, on the one hand, international efforts by multilateral and bilateral creditors and aid donors to reduce corruption in developing countries and, on the other, the role played by political corruption in promoting local accumulation of wealth, property and capital in Africa. The process of globalisation includes a concerted effort to reduce the costs and increase the predictability of international business activities. The effort has been particularly directed at countries undergoing economic restructuring and democratic change. The weak bargaining position of African states, where debt and underdevelopment make dependence on international creditors and aid donors especially acute, has led to a variety of direct, unsubtle pressures to force these states to undertake ‘governance’ reforms. While many of these measures address important problems undermining African development, they also misunderstand the nature of corruption as an African problem in two important ways.